Stress, Resilience, and Satisfaction in Families of Children with Disabilities - Llauradó, Esther Vela; Suárez Riveiro, José Manuel (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: A child’s disability can have significant consequences for the family, especially at an emotional level and in day-to-day life. Families must adapt to ever-changing circumstances, frequently leading to stress within the family. Each family member must attempt to cope with these circumstances, drawing on cognitive and behavioral resources to deal with new situations. Objectives: This work aims to study stress, resilience, and satisfaction within the families of children with and without disabilities. It also analyzed these aspects depending on the type of disability (intellectual, physical, autism spectrum disorder, and multiple disabilities). Methods: The sample consisted of 299 families, of whom 178 had a child with a disability and 121 without any disability. The study used the Parenting Stress Index – Short Form (PSI-FS) and the Saavedra-Villalta Resilience Scale (SV-RES). Satisfaction was measured using two items evaluating family satisfaction in general and the perceived satisfaction of the child in particular. Results: The results show that families having a child with a disability reported higher levels of resilience but lower levels of stress and family satisfaction. Moreover, differences were observed depending on the type of disability, with those affected by intellectual disability showing higher levels of stress and lower levels of resilience. Conclusion: The study results show the importance of resilience in dealing with adverse situations that may produce stress. This is an important aspect that must be considered in work and interventions with families of children with disabilities.